Implementasi Algoritma Fuzzy C-Means Pada Aplikasi Seleksi Karyawan Digital Talent di PT Telekomunikasi Indonesia - Desrianti, Riska; Wijaya, Herry Derajad (STMIK Budi Darma, 2020)
Digital talent is currently needed along with increasing demand for digital application projects in PT. Telekomunikasi Indonesia. The manual recruitment process is a constraint to provide the needs of digital talent. To facilitate the recruitment process is required recruitment system which implements data mining techniques to cluster candidate based on level. Fuzzy c-means is the clustering method that will be implemented on this system. The system is designed to support recruitment process and predict candidate levels. With the recruitment system, the process is expected to be faster and more accurate than before. The digital talent employees data will be used as training data with the attributes last education, certification and work experience in Information Technology. Based on the results of the study, there are 4 job-level clusters employees, namely basic, junior, medium and senior cluster.